Pemberdayaan Siswa dalam Patuh Protokol Kesehatan dengan Aksi 5M - Linda Ishariani; Laviana Nita Ludyanti (STIKES dan AKZI Karya Husada Kediri, 2022)
Covid 19 is currently still a disease that needs attention so that it does not increase again. One of the efforts is to remain obedient to the Health protocol, especially for school-age children. School-age children are an age that is still vulnerable to transmission of covid 19, so efforts are needed to prevent the spread of covid 19. One of the strategies is to empower and educate school-age children about the Health protocol with the 5M action. The purpose of this service activity is to empower, educate and socialize about the prevention of covid 19 with the Health protocol with the 5M action. The method of implementing this activity is by empowering and socializing school children. The service activities are carried out in 2 activities, namely: empowerment, education, and socialization of school children about the Health protocol with the 5M action. The result of the service activity was that a cadre/task of school children was formed to provide education and socialize with their friends about the health protocol in 5M action.